Biallelic TMEM260 variants cause truncus arteriosus, with or without renal defects. Issue 1 (11th October 2021) - Pagnamenta, Alistair T.; Jackson, Adam; Perveen, Rahat; Beaman, Glenda; Petts, Gemma; Gupta, Asheeta; Hyder, Zerin; Chung, Brian Hon‐Yin; Kan, Anita Sik‐Yau; Cheung, Ka Wang; Kerstjens‐Frederikse, Wilhelmina S.; Abbott, Kristin M.; et al.
Abstract: Only two families have been reported with biallelic TMEM260 variants segregating with structural heart defects and renal anomalies syndrome (SHDRA). With a combination of genome, exome sequencing and RNA studies, we identified eight individuals from five families with biallelic TMEM260 variants. Variants included one multi‐exon deletion, four nonsense/frameshifts, two splicing changes and one missense change. Together with the published cases, analysis of clinical data revealed ventricular septal defects (12/12), mostly secondary to truncus arteriosus (10/12), elevated creatinine levels (6/12), horse‐shoe kidneys (1/12) and renal cysts (1/12) in patients. Three pregnancies were terminated on detection of severe congenital anomalies. Six patients died between the ages of 6 weeks and 5 years. Using a range of stringencies, carrier frequency for SHDRA was estimated at 0.0007–0.007 across ancestries. In conclusion, this study confirms the genetic basis of SHDRA, expands its known mutational spectrum and clarifies its clinical features. We demonstrate that SHDRA is a severe condition associated with substantial mortality in early childhood and characterised by congenital cardiac malformations with a variable renal phenotype. Abstract :